Non-CFC refrigerants: first and second law efficienies - Sia, Chee Kiong (2002)
Concern about the ozone depletion and green house effects caused by refrigerants have initiated and continued studies into more environmentally friendly refrigerants. This study looked into the performance of these refrigerants in terms of second law efficiency, COP, irreversibility, and discharge temperature. A program based on Visual Basic has been developed that can quantify the parameters above and this can be used to guide industrialists in their efforts to build or retrofit systems with new refrigerants. Results from the simulation have shown that R134a is potentially good as a replacement for R12, R402a for R502, and R407c for R22.